Contact Angle Measurement of Small Capillary Length Liquid in Super-repelled State - Tingyi “Leo” Liu (Nature Portfolio, 2017)
Abstract The difficulty of measuring very large contact angles (>150 degrees) has become more relevant with the increased popularity of super-repellent surfaces. Measurement is more difficult for dynamic contact angles, for which theoretical profiles do not fit well, and small capillary length liquids, whose sessile droplets sag by gravity. Here, we expand the issue to the limit by investigating dynamic contact angles of liquids with an extremely small capillary length (<1.0 mm), empowered by the superomniphobic surface that can super-repel even fluorinated solvents, which highly wet all materials. Numerically simulating and experimentally testing 13 different liquids on the superomniphobic surface, we discover their dynamic contact angles can be measured with a consistent accuracy despite their vastly different capillary lengths if one keeps the lens magnification inversely proportional to the capillary length. Verifying the droplet equator height is a key parameter, we propose a new Bond number defined by the equator height and optical resolution to represent the measurement accuracy of large contact angles. Despite negligible improvement for most liquids today, the proposed approach teaches how to measure very large contact angles with consistent accuracy when any of the liquids in consideration has a capillary length below 1.0 mm.